ChemInform Abstract: Solid‐Phase Peptide Synthesis (SPPS), C‐Terminal vs. Side‐Chain Anchoring: A Reality or a Myth. Issue 40 (30th September 2014) - Cherkupally, Prabhakar; Acosta, Gerardo A.; Ramesh, Suhas; De la Torre, Beatriz G.; Govender, Thavendran; Kruger, Hendrik G.; Albericio, Fernando
Abstract Review: 75 refs.